Pengembangan Bahan Ajar Fisika Eksperimen Berbasis Proyek Untuk Meningkatkan Keterampilan Berpikir Kritis Calon Guru Fisika - Sutrio Sutrio; Gunawan Gunawan; Ahmad Harjono; Hairunnisyah Sahidu (Department of Physics Education, Universitas Mataram, 2018)
This research aims to develop project-based teaching materials of experimental Physics that can improve the critical thinking skills of prospective teachers. This research includes development of education which is divided into three phases, namely preliminary study phase, product design development phase, and product testing phase. The results showed that the teaching materials that have been developed feasible / well used in learning and meet the validation test by the expert for the contentsÃ¢â¬â¢ feasibility, presentation and language with good category. StudentsÃ¢â¬â¢ response after using the teaching materials is very good to support and complete the teaching materials at the time of lecturing. The teaching materials which tested in experimental Physics II were able to improve students' critical thinking skills from the initial test result with the mean score of 38.1 and the final test result with the mean score of 69.8.